1966
DOI: 10.1093/oxfordjournals.aob.a084066
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Defoliation on the Carbon Balance in Dactylis glomerata

Abstract: Measurements were made of the carbon dioxide exchange of roots and shoots, changes in soluble carbohydrates, rates of root extension, and rate of phosphorus uptake of young plants of Dactylis glomerata (Cocksfoot) during eight days following defoliation. The results indicated that the soluble carbohydrates formed part of a labile pool which was used in respiration and for providing substrates for new growth. Where defoliation was not severe, the changes in reserve carbohydrates could account for net respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
92
3
8

Year Published

1972
1972
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(114 citation statements)
references
References 8 publications
11
92
3
8
Order By: Relevance
“…Thus, leaf growth seems to be much more dependent on continued assimilation of carbon, which agrees well with results on carbon allocation shortly after severe defoliation: most carbon used for leaf growth was new (Avice et al, 1996;Schnyder and de Visser, 1999), while that sustaining root respiration was largely old (Avice et al, 1996). Indeed, rapid and drastic decrease of root respiration following defoliation (Davidson and Milthorpe, 1966b) may be due to the fact that substrate for root respiration is essentially derived from current CO 2 fixation and stores in the shoot. Thus, the localization of most of the respiratory substrate in the shoot indicates that the control of root activity by the shoot would occur via the control of both current photosynthate and storage mobilization.…”
Section: The Role Of Stores and Current Photosynthesis In Supplying Rsupporting
confidence: 83%
“…Thus, leaf growth seems to be much more dependent on continued assimilation of carbon, which agrees well with results on carbon allocation shortly after severe defoliation: most carbon used for leaf growth was new (Avice et al, 1996;Schnyder and de Visser, 1999), while that sustaining root respiration was largely old (Avice et al, 1996). Indeed, rapid and drastic decrease of root respiration following defoliation (Davidson and Milthorpe, 1966b) may be due to the fact that substrate for root respiration is essentially derived from current CO 2 fixation and stores in the shoot. Thus, the localization of most of the respiratory substrate in the shoot indicates that the control of root activity by the shoot would occur via the control of both current photosynthate and storage mobilization.…”
Section: The Role Of Stores and Current Photosynthesis In Supplying Rsupporting
confidence: 83%
“…It plays an important role as forage material in North America, Europe (Casler et al, 2000), and Oceania, as well as in grassland animal husbandry and ecological construction of southern subtropical mountains of China. Because of the importance of orchardgrass as a forage and hay grass, in recent years, a number of studies have been performed to examine orchardgrass morphology (Felfoldi, 1975;Turner et al, 2012), anatomy (Ashenden, 1978), cytology (Lentz et al, 1983;Tosun et al, 1999), physiology (Davidson and Milthorpe, 1966;Yoshida and Uemura, 1984;Volaire, 1995;Volaire and Lelièvre, 2001), ecology (Eagles, 1983;Fan, 1997;Kyriazopoulos et al, 2013), and breeding (Denchev et al, 1997;Casler et al, 2000;Hopkins and Bhamidimarri, 2009). Molecular-level studies of orchardgrass have also been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Often no definite trends in organic nitrogen level are evident, as there are with carbohydrates; however, Dilz (1966) in studying perennial ryegrass (Lolium perenne L.), concluded that proteinaceous material should be regarded as reserve constituents. Davidson and Milthorpe (1966) concluded that nonstructural carbohydrates formed only a part of the labile pool which provided substrates for respiration and new growth of orchardgrass (Dactylis glomerata L.). They suggested that proteins must have been remobilized because the amount of nonstructurd carbohydrates was inadequate to account for respiration and new growth of roots and shoots following severe herbage removal.…”
mentioning
confidence: 99%